2015
DOI: 10.1111/jfpe.12249
|View full text |Cite
|
Sign up to set email alerts
|

Heat Processing of Blueberries and Its Effect on Their Physicochemical and Bioactive Properties

Abstract: The current study aimed to evaluate the dehydration process of blueberry fruits at temperatures of 70, 80 and 90C and its effect on their physicochemical and bioactive properties. The values for moisture content and water activity (aw) were still high for dehydrated fruits, although at temperatures of 80 and 90C, the dried fruits showed a aw below the limit for contamination by pathogenic microorganisms. The antioxidant activity increased during the first half of dehydration at 80C, but after 3 h suffered a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Dried blueberries can be stored at room temperature. Whereas conventional thermal dehydration can cause significant losses to anthocyanins ( 182 ), freeze-drying is an excellent means to remove water while preserving blueberry phytochemical quality ( 183 ). Freeze-dried blueberry powder loses anthocyanins in a temperature-dependent manner with a half-life of 139, 39, and 12 d when stored at 25, 42, and 60°C, respectively ( 184 ).…”
Section: Blueberries Anthocyanins and Food Processingmentioning
confidence: 99%
“…Dried blueberries can be stored at room temperature. Whereas conventional thermal dehydration can cause significant losses to anthocyanins ( 182 ), freeze-drying is an excellent means to remove water while preserving blueberry phytochemical quality ( 183 ). Freeze-dried blueberry powder loses anthocyanins in a temperature-dependent manner with a half-life of 139, 39, and 12 d when stored at 25, 42, and 60°C, respectively ( 184 ).…”
Section: Blueberries Anthocyanins and Food Processingmentioning
confidence: 99%
“…Required moisture values were reached after drying for 11 h at 60°C, 9 h at 70°C, and 7 h at 80°C, and no difference was found between chlorinated and nonchlorinated samples. Reque et al (2015) demonstrated that the dehydration of blueberry fruit at 80 or 90°C led to moisture values below the limit for pathogenic microorganism contamination. On the other hand, they found that longer heat processing times caused a decrease in the bioactive and antioxidant properties of dried blueberry fruit.…”
Section: Drying Curves Of Beetroot Waste Flourmentioning
confidence: 99%
“…Blueberry fruits contain high concentrations of bioactive components, such as procyanidins, anthocyanins, flavonols, and chlorogenic acid. These components have antimicrobial, antioxidant, anticancer, antidiabetic, and cardioprotective activities. Blueberry is a popular fruit worldwide for its high nutritional value and health benefits.…”
Section: Introductionmentioning
confidence: 99%